Assessment of thirty‐day readmission rate, timing, causes and predictors after hospitalization with COVID‐19. (5th February 2021) - Yeo, I.; Baek, S.; Kim, J.; Elshakh, H.; Voronina, A.; Lou, M.S.; Vapnik, J.; Kaler, R.; Dai, X.; Goldbarg, S.
Abstract: Background: There are limited data on the characteristics of 30‐day readmission after hospitalization with coronavirus disease 2019 (COVID‐19). Objectives: To examine the rate, timing, causes, predictors and outcomes of 30‐day readmission after COVID‐19 hospitalization. Methods: From 13 March to 9 April 2020, all patients hospitalized with COVID‐19 and discharged alive were included in this retrospective observational study. Multivariable logistic regression was used to identify the predictors of 30‐day readmission, and a restricted cubic spline function was utilized to assess the linearity of the association between continuous predictors and 30‐day readmission. Results: A total of 1062 patients were included in the analysis, with a median follow‐up time of 62 days. The mean age of patients was 56.5 years, and 40.5% were women. At the end of the study, a total of 48 (4.5%) patients were readmitted within 30 days of discharge, and a median time to readmission was 5 days. The most common primary diagnosis of 30‐day readmission was a hypoxic respiratory failure (68.8%) followed by thromboembolism (12.5%) and sepsis (6.3%). The patients with a peak serum creatinine level of ≥1.29 mg/dL during the index hospitalization, compared to those with a creatinine of <1.29 mg/dL, had 2.4 times increased risk of 30‐day readmission (adjusted odds ratio: 2.41; 95% CI: 1.23–4.74). The mortality rate during the readmission was 22.9%. Conclusion: With 4.5% of the thirty‐day readmission rate, COVID‐19 survivors were readmitted early after hospital discharge, mainly due to morbidities of COVID‐19. One in five readmitted COVID‐19 survivors died during their readmission. Abstract :